Rethinking Political Moderation in Indonesia: A Critique from Chantal Mouffe’s Agonistic-Pluralism Perspective - Musthafa, Adib Khairil; Rofiq, Muhammad Ainun; Zahara, Alfan Nawaziru (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
This article serves as a critical response to the work of Syahrain et al., which advocates for political moderation as the new foundation of Indonesian democracy. Utilizing Chantal Mouffe’s framework of agonistic pluralism, this study challenges the foundational assumptions of consensus-based deliberative democracy, which is thought to restore social cohesion. The article contends that such a model of moderation can reinforce dominant power, obscure significant differences of opinion, and constrict the political participation space for opposition or minority groups. Employing a qualitative-descriptive method, the article examines the literature on democratic theory and reflects on the cases of the 2017 Jakarta regional election (Pilkada DKI) and the 2019 presidential election (Pilpres). Data were collected from academic studies, policy documents, and media reports. The findings indicate that the rhetoric of moderation, which emphasizes harmony and stability, actually diminishes the space for ideological opposition; the delegitimization and dissolution of HTI and FPI affirm this tendency. Such practices not only consolidate the hegemony of dominant power but also exacerbate inequalities in political participation. As an alternative, we propose agonistic democracy: a model that recognizes conflict and difference as prerequisites for a vibrant public sphere. Its implementation includes reforming party systems based on proportional representation, providing legal protections for minority political groups, and designing public policies that accommodate the contestation of ideas. This approach aims to balance stability with political expression, ensuring that critical voices and marginalized alternative identities are not suppressed at the national level. Thus, this article advocates for a new paradigm of Indonesian democracy that is more inclusive, equitable, and resilient to diverse identities and political visions. Abstrak: Artikel ini merupakan respons kritis terhadap tulisan Syahrain et al. yang mengusung moderasi politik sebagai fondasi baru demokrasi Indonesia. Berbekal kerangka pluralisme agonistik Chantal Mouffe, studi ini mempertanyakan asumsi dasar demokrasi deliberatif berbasis konsensus yang diasumsikan mampu memulihkan kohesi sosial. Artikel ini berargumen bahwa model moderasi seperti itu bisa memperkuat kekuasaan yang dominan, menghilangkan perbedaan pandangan yang tajam, dan menyempitkan ruang partisipasi politik bagi kelompok oposisi atau minoritas. Melalui metode kualitatif‑deskriptif, artikel ini menelaah literatur teori demokrasi dan merefleksikannya pada kasus Pilkada DKI 2017 serta Pilpres 2019. Data dihimpun dari kajian akademik, dokumen kebijakan, dan laporan media. Temuan mengindikasikan bahwa retorika moderasi, yang menekankan harmoni dan stabilitas, justru menyusutkan ruang oposisi ideologis; delegitimasi hingga pembubaran HTI dan FPI menegaskan kecenderungan ini. Praktik tersebut tidak hanya meneguhkan hegemoni kekuasaan dominan, tetapi juga menggandakan ketimpangan partisipasi politik. Sebagai alternatif, kami mengusulkan demokrasi agonistik: model yang mengakui konflik dan perbedaan sebagai prasyarat ruang publik. Implementasinya meliputi reformasi sistem kepartaian berbasis representasi proporsional, perlindungan hukum bagi kelompok politik minoritas, dan perancangan kebijakan publik yang membuka lintasan kontestasi ide. Pendekatan ini bertujuan menyeimbangkan stabilitas dan ekspresi politik tanpa menindas suara kritis serta identitas alternatif marginal di level nasional. Dengan demikian, artikel ini mendorong paradigma baru demokrasi Indonesia yang lebih inklusif, setara, dan resilien terhadap pluralitas identitas maupun visi politik.